An Efficient and Simple Method for Collecting Haemolymph of Cerambycidae (Insecta: Coleoptera) Adults - Yiming Niu; Yuxuan Zhao; Fengming Shi; Meng Li; Sainan Zhang; Jinglin Yang; Shixiang Zong; Jing Tao (Insects, 2022)
Cerambycid beetles (Cerambycidae) are major forest pests, posing a serious threat to the security of forest resources worldwide. Extensive research has focused on the control of cerambycid beetles from physiological and biochemical perspectives. Despite the important roles of insect haemolymph in physiological processes, efficient collection methods for Cerambycidae are lacking. For the efficient and easy collection of large amounts of pure haemolymph from adult cerambycid beetles, a new method, named net centrifugation, was developed. Three species of cerambycid beetles with large differences in size, Anoplophora chinensis, Monochamus saltuarius and Saperda populnea, were selected for the study. Haemolymph was collected by the newly developed net centrifugation method—in which an inner nylon net is used during centrifugation under optimised conditions, and a relatively small wound is generated on the insect—as well as the traditional tearing method and double centrifugation method. Among the three methods evaluated, the net centrifugation method caused the least damage to cerambycid beetles during the whole operation. This method resulted in the most haemolymph from a single beetle, with the lowest turbidity, mostly pure haemocytes in the precipitate, the clearest haemolymph smears by microscopy and the highest quality of RNA extracted from haemocytes. The net centrifugation method has a high collection efficiency, providing important technical support for haemolymph extraction and entomological research.